Cerebrovascular Resistance: The Basis of Cerebrovascular Reactivity - Duffin, James; Sobczyk, Olivia; McKetton, Larissa; Crawley, Adrian; Poublanc, Julien; Venkatraghavan, Lashmi; Sam, Kevin; Mutch, W. Alan; Mikulis, David; Fisher, Joseph A. (Frontiers in Neuroscience, 2018)
The cerebral vascular network regulates blood flow distribution by adjusting vessel diameters, and consequently resistance to flow, in response to metabolic demands (neurovascular coupling) and changes in perfusion pressure (autoregulation). Deliberate changes in carbon dioxide (CO2) partial pressure may be used to challenge this regulation and assess its performance since CO2 also acts to change vessel diameter. Cerebrovascular reactivity (CVR), the ratio of cerebral blood flow (CBF) response to CO2 stimulus is currently used as a performance metric. However, the ability of CVR to reflect the responsiveness of a particular vascular region is confounded by that region’s inclusion in the cerebral vascular network, where all regions respond to the global CO2 stimulus. Consequently, local CBF responses reflect not only changes in the local vascular resistance but also the effect of changes in local perfusion pressure resulting from redistribution of flow within the network. As a result, the CBF responses to CO2 take on various nonlinear patterns that are not well described by straight lines. We propose a method using a simple model to convert these CBF response patterns to the pattern of resistance responses that underlie them. The model, which has been used previously to explain the steal phenomenon, consists of two vascular branches in parallel fed by a major artery with a fixed resistance unchanging with CO2. One branch has a reference resistance with a sigmoidal response to CO2, representative of a voxel with a robust response. The other branch has a CBF equal to the measured CBF response to CO2 of any voxel under examination. Using the model to calculate resistance response patterns of the examined branch showed sigmoidal patterns of resistance response, regardless of the measured CBF response patterns. The sigmoid parameters of the resistance response pattern of examined voxels may be mapped to their anatomical location. We show an example for a healthy subject and for a steno-occlusive patient to illustrate. We suggest that these maps provide physiological insight into the regulation of cerebral blood flow distribution.